The case against physician-assisted suicide and voluntary active euthanasia: A jurisprudential consideration - TAN, Seow Hon (Institutional Knowledge at Singapore Management University, 2017)
Twenty years after the Advance Medical DirectiveAct came into force in Singapore, the issue of the legalisation ofphysician-assisted suicide and voluntary active euthanasia remains live. Thisarticle examines the case for legalisation, replying to the points raised inthe article by Toh Puay San and Stanley Yeo, “Decriminalisingphysician-assisted suicide in Singapore” (2010) 22 SAcLJ 379–412, which hadincluded draft legislation in its proposal. It critically discusses thetheoretical underpinnings of such legalisation and argues that the contentionof the authors that the benefits of allowing terminally-ill patients the optionof physician-assisted suicide far outweigh the harms is not supported. Afortiori, voluntary active euthanasia should not be legalised.